1999
DOI: 10.1034/j.1399-0012.1999.130410.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient survival after renal transplantation: II. The impact of smoking

Abstract: Renal transplant recipients have significantly higher mortality than individuals without kidney disease and the excess mortality is mainly due to cardiovascular causes. In this study, we sought to determine the impact of smoking, a major cardiovascular risk factor, on patient and renal graft survival. The study population included all adult recipients of first cadaveric kidney transplants done in our institution from 1984 to 1991. By selection, all patients were alive and had a functioning graft for at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 22 publications
3
39
1
1
Order By: Relevance
“…The data document that smoking is by far the strongest modifiable predictor of mortality in these elderly patients. These data have largely been confirmed by others (104), even in younger individuals (102). The magnitude of the negative effect of pretransplantation smoking is quantitatively similar to that of diabetes (102).…”
Section: Patients With a Renal Transplantsupporting
confidence: 76%
“…The data document that smoking is by far the strongest modifiable predictor of mortality in these elderly patients. These data have largely been confirmed by others (104), even in younger individuals (102). The magnitude of the negative effect of pretransplantation smoking is quantitatively similar to that of diabetes (102).…”
Section: Patients With a Renal Transplantsupporting
confidence: 76%
“…This finding can be attributed to the high percentage of transplant recipients with hypertension both before and after transplantation, which makes this factor have little discriminating capacity, or to the systematic treatment of hypertension that reduces the adverse effects in this population. Cigarette smoking has been associated with posttransplantation IHD (6,7,10) and with mortality (24,25). Our data confirmed the association between smoking and IHD.…”
Section: Discussionsupporting
confidence: 79%
“…These reports suggest that active smoking is a potential risk factor for graft loss [24][25][26][27] and mortality. 25,28 A retrospective cohort study comprising 1334 renal transplant recipients at the Henepin County Medical Center in the United States found that a smoking history of 425 pack-years was significantly associated with a 30% increase in risk of graft failure, whereas a history of o25 pack-years did not affect graft survival. 25 This study also suggested that the higher rate of graft loss in recipients with a history of heavy smoking was caused by higher mortality as compared with non-smokers.…”
Section: Smoking and Ckd In Patients With Renal Transplantsmentioning
confidence: 99%